Home and away: Family matters in the lives of young transnational couples. (September 2014) - McLeod, Danae; Burrows, Roger
The institutional mechanisms by which young adults come to experience temporary periods of global mobility are varied, but what most have in common is a presupposition that those gaining entry into another country will return 'home' within a specific period. This article is concerned to better understand how young adults who are engaged in such forms of global travel manage the significant personal emotional intimate attachments that many of them make in the places that they visit when a decision has to be made about returning. Here we offer an empirical examination of what happens when an envisaged return 'home' is stymied by the formation of a significant intimate relationship with someone from another country. In particular we focus on the role that 'family matters' play in decision-making processes.